UANG DAN RELEVANSINYA PADA LEMBAGA KEUANGAN SYARIAH MENURUT AL GHAZALI - Amri, Ulil; Yuda, Adam Damba (Islamic Economics Program, Faculty of Islamic Economics and Business, 2021)
This study aims to determine the relevance of Al Ghazali's perspective on money in Islamic financial institutions. In this case, Al Ghazali argues that someone who hoards money is an act that is unjust and has removed the function of the money. The research method used in this research is to use qualitative methods. The author conducted in-depth interviews or interviews with several sources including from Islamic banking and Baitul Mal at Tamwil to obtain primary data. Based on the results of the study that the savings products that exist in Islamic financial institutions in this study Islamic banking and baitul mal at Tamwil cannot be said to be hoarding assets. There is an intermediation function in Islamic financial institutions, namely bringing together people who have excess money (people who save) and people who lack money (loan products).